Latino-americanos e europeus no Brasil: analisando processos migratórios e identitários no Estado do Espírito Santo - Brasil, Julia Alves (2012)
Nowadays, with the phenomenon of globalization, we have witnessed several global changes such as the bigger connection between different regions and countries of the world. One of the most relevant aspects of this process is the migration of people from one country to another. This way, considering the importance of the migratory fluxes for the constitution of the Brazilian population, this research aimed to know the identity processes bind to Latin American and European immigrants who have moved to Brazil - including people who are descendants of these nationalities – who currently live in the state of Espírito Santo. Therefore, having the referential of the Social Identity Theory (SIT) as a starting point, 37 interviews were made (14 Latin Americans, 6 Latin American descendants, 12 Europeans, and 5 Europeans descendants) with participants of both sexes and older than 18 years. The script used was a semi-structured one, containing social-demographic data as well as questions regarding the reasons of migration, the process of adaptation to Brazil and the stereotypes about Brazilian society and the native country of the migrants. The data were organized through the ALCESTE software and Content Analysis. The results indicate that there are differences in the migration and identity processes of Latin Americans and Europeans – for these, their coming to Brazil was a result of romantic relationships established here; but for those, their coming was motivated by the existence of available resources such as scholarships in the country. The insertion and adaptation of these foreigners to Brazil is also differentiated between them – the Europeans having experienced appreciation from the Brazilian people, while many Latin Americans reported having gone through discriminative situations. Both groups of immigrants and their descendants experiment a constant dialogue between different cultures and tend to value positively their group of belonging, considering that this membership might be multiple and vary according to the different contexts of insertion. In that sense, whether they are immigrants or descendants, Europeans or Latin Americans, the individuals’ biggest goal regarding the process of building an identity is preserving their positive social distinctiveness, making use of strategies which they find appropriate to each situation in order to achieve that purpose. Stands out the importance of the conduction of further studies – especially in the Social Psychology field – about international migrations and which consider the complexity of such event, approaching it in a broad and multidisciplinary way, in order to contribute to the construction of more coherent public policies with the reality experienced by immigrants and descendants, not only in the state of Espírito Santo, but all over Brazil.